A Study on the Role of Lactulose on Hepatic Encephalopathy Among Cirrhotic Patients with Acute Upper Gastrointestinal Bleeding - Asfand-E-Yar Khan, Rashid Karim, Ehsan Rahim Memon, Amna Asghar, Hafiz Muhammad Imran Aziz, Waqas Qurshi (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the efficacy of lactulose as prophylaxis on hepatic encephalopathy among cirrhotic patients of acute upper gastrointestinal bleeding. Material and methods: We carried out this randomized control trial in multi centers including Mian Rashid Hussain Shaheed Memorial Hospital Pabbi Nowshera. KPK and Isra University Hospital, Hyderabad from February 2022 to July 2022 (06 months) with total no of 80 patients. Group A patients received lactulose while group B patients received sweet syrup placebo. Both groups were assessed for Hepatic encephalopathy as primary outcome. Chi Square test was used for assessment of outcomes between both groups keeping P value < 0.05 as statistically significant. Results: Eighty patients were divided into two groups equally using lottery method. Group A patients received lactulose treatment while group B patients received placebo. The mean age in group A was 44.36±15.37 years while the mean age in group B was 38.71±18.56 years. Hepatic encephalopathy was observed in 2.5% patients in group A while in group B 10% patients had HE, the difference was statistically significant. Diarrhea, abdominal pain and mortality between both groups were no statistically significant. Conclusion: Lactulose is effective in preventing hepatic encephalopathy in patients with cirrhosis and an acute upper gastrointestinal bleeding. Keywords: Lactulose, hepatic encephalopathy, cirrhosis, acute upper gastrointestinal bleeding